Interval training and the GH-IGF-I axis - a new look into an old training regimen - Eliakim, A.; Nemet, D. (Journal of Pediatric Endocrinology and Metabolism, 2012)
Interval training is a commonly used training method known to improve both aerobic and anaerobic capabilities, and is one of the popular techniques used in training young athletes engaged in both anaerobic- and aerobic-type sports. This occurs although anaerobic glycolytic capacity is less efficient in the child and becomes increasingly more effective with age. The endocrine system, by modulation of anabolic and catabolic processes, plays a major role in the physiological adaptation to exercise training. In recent years, changes in circulating components of the growth hormone-insulin-like growth factor-1 axis, a system of growth mediators that control somatic and tissue growth, have been used to quantify the effects of training. Interestingly, exercise is also associated with remarkable changes in inflammatory cytokines, and the exercise-related response of these markers can also be used to gauge exercise load. The balance between these two seemingly antagonistic systems is believed to determine the effects of exercise. This review will summarize current knowledge on the balance of anabolic hormones and inflammatory mediators following anaerobic, interval exercise and training and its implication to young athletes.